Implementasi Algoritma Rice Code dan Ternary Comma Code Pada Kompresi File PDF - Ade Novian Purnama (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Currently, the source of information obtained is not only through print media but also electronic media such as e-books (digital books). E-books can be accessed on laptops, tablets, smartphones and other electronic media. Usually the e-book file used is with a PDF extension. PDF as an eBook extension has its deficiency. The deficiency of PDF is a format that does a little compresion, causing e-books with PDF extensions to have a fairly large size. This causes the process of reading data and sending data takes quite a long time, and often fail during the delivery process.To solve the size of the PDF file that is large enough, compression process is required. Compression is a new data compression process that has a smaller size in the form of a character set with the aim of saving storage space requirements and speeding up the data scanning process. Therefore, the Rice Code and Ternary Comma Code algorithms are used, both of which are applied sequentially (double compression) so that files can be compressed with a maximum size.The final result of the double compression process by the Rice Code and Ternary Comma Code algorithms carried out by the author obtained a Compression Rate (CR) value of 20%, which means that the initial PDF file size can be compressed until its size only reaches 20% of the original PDF file size